2016
DOI: 10.1002/pro.2969
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain salt‐bridges in the Ebola virus protein VP40 and their role in domain association and plasma membrane localization

Abstract: The Ebola virus protein VP40 is a transformer protein that possesses an extraordinary ability to accomplish multiple functions by transforming into various oligomeric conformations. The disengagement of the C-terminal domain (CTD) from the N-terminal domain (NTD) is a crucial step in the conformational transformations of VP40 from the dimeric form to the hexameric form or octameric ring structure. Here, we use various molecular dynamics (MD) simulations to investigate the dynamics of the VP40 protein and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…(C)]. Lastly we investigated plausible salt bridges formed at the interface of ARID and PHD1 domains, because salt bridges are frequently observed at transient domain‐domain interfaces . Since we had previously performed 5 parallel runs, we only selected the salt‐bridges observed in no less than two runs.…”
Section: Resultsmentioning
confidence: 99%
“…(C)]. Lastly we investigated plausible salt bridges formed at the interface of ARID and PHD1 domains, because salt bridges are frequently observed at transient domain‐domain interfaces . Since we had previously performed 5 parallel runs, we only selected the salt‐bridges observed in no less than two runs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we showed that WWP1-WT ubiquitinated eVP40 and that the presence of higher-molecular-weight (MW) oligomers of eVP40 was reduced significantly in the presence of WWP1-WT but not in the presence of WWP1-C890A. These findings indicate that a functional interaction between eVP40 and WWP1 leads to eVP40 ubiquitination, likely promoting more efficient self-assembly, maturation, and scission of eVP40 VLPs from the plasma membrane (58)(59)(60)(61).…”
mentioning
confidence: 82%
“…The identity of the mutants was concealed during imaging to minimize bias. Heterologous expression levels were confirmed via western blot as previously described (59).…”
Section: Cell Culture and Cell Imagingmentioning
confidence: 99%